Scientific Initiation in the interior of the Amazon: promoting scientific and technological literacy with elementary students in a Science club (Research, Society and Development, 2020)
The present work aims to investigate the contributions of the Scientific Initiation to the promotion of Scientific and Technological Literacy of primary school students. In addition, it intends to socialize research activities, developed in a Science Club, with students of elementary and secondary education and to disseminate Scientific Initiation as an educational possibility to the school environment. The moments of planning, execution and socialization of the projects served as sources of information for the collection of data that are analyzed following the guidelines of Bardin (2011).The study revealed that Scientific Initiation is a path that can offer conditions for the individual to acquire the conceptual content, in a significant way, because it does not privilege it, placing it at the same level of importance of the procedural, epistemological and attitudinal contents, thus corroborating, for the broad development of students and the promotion of Scientific and Technological Literacy of the same.